Microfluidic-Based F-Labeling of Biomolecules for Immuno–Positron Emission Tomography - Kan Liu; Eric J. Lepin; Ming-Wei Wang; Feng Guo; Wei-Yu Lin; Yi-Chun Chen; Shannon J. Sirk; Sebastian Olma; Michael E. Phelps; Xing-Zhong Zhao; Hsian-Rong Tseng; R. Michael van Dam; et al. (Molecular Imaging)
Methods for tagging biomolecules with fluorine 18 as immuno–positron emission tomography (immunoPET) tracers require tedious optimization of radiolabeling conditions and can consume large amounts of scarce biomolecules. We describe an improved method using a digital microfluidic droplet generation (DMDG) chip, which provides computer-controlled metering and mixing of 18 F tag, biomolecule, and buffer in defined ratios, allowing rapid scouting of reaction conditions in nanoliter volumes. The identified optimized conditions were then translated to bench-scale 18 F labeling of a cancer-specific engineered antibody fragments, enabling microPET imaging of tumors in xenografted mice at 0.5 to 4 hours postinjection.